EFEKTIVITAS WADAH BUNDAR BERARUS TERHADAP PENINGKATAN RESPON IMUN BENIH IKAN MAS (Cyprinus carpio) YANG DIINFEKSI OLEH BAKTERI Aeromonas hydrophila - Ibnu Bangkit Bioshina Suryadi; Zaqi Rachman Sidqi; Roffi Grandiosa; Walim Lili (Jurnal Akuakultur Rawa Indonesia, 2022)
This research focused on determining the best survival performance of carp (C. carpio) fingerlings in circular containers combined with venturi aerators to generate water current, then challenged by A. hydrophila. The research used an experimental method of Completely Randomized Design (CRD) with four treatments and four replications. The treatment used was the use of venturi aerators on circular containers: without water current as a control (A), with a water current of 0.06 ms?¹ (B), 0.1 ms?¹ (C), and 0.14 ms?¹ (D). The study was initiated by rearing 5-7 cm fish fingerlings for 40 days and followed by a challenge test for 14 days. Carp fingerlings were challenged by A. hydrophila intraperitoneally at a density of 10? CFU ml?¹. Each tank consists of 15 fingerlings. Parameters observed included survival rate, the number of red blood cells and white blood cells, macroscopic symptoms, and water quality. The results showed survival rate in treatment (D) was the best (water current of 0.14 ms?¹), 98% before the challenge period and 95% after the challenge period. In addition, it can increase the hematological parameters as seen from the increase in the number of red and white blood cells after the challenge test, from 1.043 x 106 cells mm³?¹ to 2.36 x 106 cells mm³?¹ and 2.7 x 104 cells mm³?¹ to 9.3 x 104 cells mm³?¹ respectively. And it shows an increased immune response as seen from the recovery acceleration in macroscopic symptoms on the seventh day after A. hydrophila injection. While water quality did not differ between control and treatments.Keywords : current circular generating tank, carp fingerling, Aeromonas hydrophila, immune response